STATUS KEGEMUKAN, ASUPAN NATRIUM DAN TEKANAN DARAH SISTOLIK PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS I DENPASAR TIMUR - Ni Kadek Wilandari Saputri; Hertog Nursanyoto; Ida Ayu Eka Padmiari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. One of the triggers for hypertension is obesity status and sodium intake. This study aims to determine the relationship of obesity status, sodium intake, and systolic blood pressure in patients with hypertension in the working area of Puskesmas I Denpasar Timur . This type of research is Observational with cross sectional research design. This research was conducted in March 2020, taken by the Perposive Sampling method of 30 people. Systolic blood pressure samples were measured using a tensimeter cuff (sphygmomanometer) and a stethoscope, obesity status was determined based on Height and Weight, and sodium intake was obtained through interviews using a 1x24 hour recall form. Data were analyzed using the Mann-Whitney test. A total of 76.7% of the sample was nutritional status of fat, 66.7% of the samples with less sodium intake category and 86.7% of the samples had grade 1 hypertension status. Based on the results of the analysis, there were known trends in systolic blood pressure differences based on nutritional status and sodium intake, the statistical difference was not significant (p 0.05). Expected to pay more attention and maintain systolic blood pressure by conducting regular checks. Keywords: Systolic Blood Pressure, Obesity Status and Natrium Intake.